Sosialisasi Pencegahan dan Penanggulan Penyakit Demam Berdarah dan Menciptakan Lingkungan Yang Bersih di Lingkungan Rw.034 Desa Sumber Jaya, Kab. Bekasi - Sjarifudin, Didin; Ripai, Ahmad; Wisnu, Raja Dewa; Najib, Anang Khoiri; Adriansyah, Putra; Taufik, Muhammad; Sunardi, Lingga Putra; Astrianto, Alfian Putra; Ramdani, Umar; Tarmizi, Khanan Habib; Gifary, Fiqri Raihan Al (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2025)
The Real Work Lecture Program conducted by Group 5 has the goal of socializing and striving to increase public awareness in Sumber Jaya Village, especially in RW 034 in terms of clean-living behavior and prevention of Dengue Hemorrhagic Fever (DHF). The KKN program that will be carried out consists of the main activities in the form of community service, socialization about a healthy environment and dengue disease as well as the provision of lavender plants, making plant naming around the RW 034 post with QR Code, socialization for children with piggy bank painting media, and making an inorganic waste bank. Through these programs, it is hoped that it can increase public awareness of healthy living with a clean environment, expand public knowledge about dengue disease more deeply, use technology media in the form of SCcan QR Code as a development of education for local residents about plants and their uses, increase awareness of clean living for children from an early age, and foster awareness of the importance of waste management to support efforts to improve lives healthy in preventing dengue. From the activities that have been carried out, it turns out that the KKN carried out by Group 5 in Sumber Jaya village has succeeded in having a positive impact on the community and the environment.